Composite material for high‐temperature thermochemical energy storage using calcium hydroxide and ceramic foam. Issue 2 (13th May 2019) - Funayama, Shigehiko; Takasu, Hiroki; Zamengo, Massimiliano; Kariya, Jun; Kim, Seon Tae; Kato, Yukitaka
Abstract: Thermochemical energy storage using a calcium oxide/calcium hydroxide/water (CaO/Ca(OH)2 /H2 O) reaction system is a promising technology for thermal energy storage at high‐temperatures (400°C‐600°C). The purpose of this study is to develop a practical composite material by enhancing heat transfer through the reaction bed and mitigating problems of pure CaO/Ca(OH)2 materials, such as formation of centimeter‐scale agglomerates and change in the bulk volume during repetitive reactions. The present study focused on a novel composite material using a silicon carbide/silicon (SiC/Si) foam. In the literature, performance of thermochemical energy storage of the composite using the ceramic foam remains unclear. In this study, we evaluated the performance of the composite material (~63 g) by a 100‐W‐scale packed bed reactor. The volumetric heat output rate (for the first 5 minutes, under maximum hydration pressure) of the composite was 1.3 kW L‐bed −1, which was 1.4 times higher than that previously reported for a bed of pure Ca(OH)2 pellets. The composite material, in which the CaO/Ca(OH)2 samples were subdivided inside pores with a mean diameter of 400 μm, retained high reactivity during cycle reactions, and maintained its bulk volume. Therefore, the composite material developed in this study shows promising application for high‐temperature thermochemical energy storage.